2008
DOI: 10.3748/wjg.14.2968
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approach to acute pancreatitis

Abstract: The aim of the present review is to summarize the current knowledge regarding pharmacological prevention and treatment of acute pancreatitis (AP) based on experimental animal models and clinical trials. Somatostatin (SS) and octreotide inhibit the exocrine production of pancreatic enzymes and may be useful as prophylaxis against post endoscopic retrograde cholangiopancreatography pancreatitis (PEP). The protease inhibitor gabexate mesilate (GM) is used routinely as treatment to AP in some countries, but random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 104 publications
1
41
0
5
Order By: Relevance
“…Although the other three scores did not show any significant difference, a decrease in inflammation and perivascular infiltrate score by 35% in experimental rat models with cerulein-induced acute pancreatitis administered with one dose of everolimus by oral gavage and a decrease by 75% in those administered with two doses of everolimus were the most significant and promising findings of this study (Table 4). Because the mortality rate significantly increases with multiple organ failure because of SIRS, the specific inhibition of inflammatory signalling pathways presents a great potential as pharmacological treatment (2,6,21). The significant decrease in inflammation and perivascular infiltrate score may imply that everolimus treatment directly or indirectly interferes with the inflammatory signalling pathway, thereby inhibiting SIRS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the other three scores did not show any significant difference, a decrease in inflammation and perivascular infiltrate score by 35% in experimental rat models with cerulein-induced acute pancreatitis administered with one dose of everolimus by oral gavage and a decrease by 75% in those administered with two doses of everolimus were the most significant and promising findings of this study (Table 4). Because the mortality rate significantly increases with multiple organ failure because of SIRS, the specific inhibition of inflammatory signalling pathways presents a great potential as pharmacological treatment (2,6,21). The significant decrease in inflammation and perivascular infiltrate score may imply that everolimus treatment directly or indirectly interferes with the inflammatory signalling pathway, thereby inhibiting SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a number of pharmacological approaches, which are mostly supportive involving adequate fluid resuscitation and oxygen supplementation, to maintain normal arterial oxygen saturation (6,7). However, when the local inflammation of pancreas provokes the systemic inflammatory response syndrome (SIRS), the treatment requires intensive medical management and even surgery (3-5, 8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…In another study,a reduction in complication frequency and mortality rates has been reported after a 7-day infusion treatment with 2400mg/day dose of gabexatemesilate [60].Hence, the use of protease inhibitors in severe acute pancreatitis is currently controversial. While the ability of somatostatin and its analog octreotide to suppress the exocrine secretions of the pancreas, and therefore rest the inflamed pancreatic tissue has caused therapeutic expectations, their efficiency was not demonstrated except for a single study [61,62].Somatostatin and octreotide have been reported to reduce mortality only in severe acute pancreatitis in a single meta analysis [63],the current notion does not recommend their use in treatment with respect to cost-effectiveness.…”
Section: Antibiotic Treatment and Other Treatmentsmentioning
confidence: 99%
“…Like most corticosteroids, methylprednisolone is typically used for its anti-inflammatory effects. The function of etanercept plus MP is unclear as a therapeutic agent in the prevention and treatment of AP (Bang et al, 2008). The purpose of present study was to investigate whether the combined effects of etanercept plus MP could prevent, or decrease pancreatic oxidative stress in cerulein-induced AP, as defined by the markers of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality due to AP is approximately 10%, but this estimate raise up to 20-30% in the severe forms of the disease due to multiple organ failure. Progress in medicine, mostly supportive and antibiotic therapy and surgery all has contributed to reduce mortality and morbidity rates in severe AP in the past decades (Pereda et al, 2006;Bang et al, 2008;Steer, 2008). However, no specific effective treatment has been reported in the clinical trials so far.…”
Section: Introductionmentioning
confidence: 99%